Impacts of Hydro-Climatically Varying Years on Ice Growth and Decay in a Subarctic River - Eliisa Lotsari; Lovisa Lind; Maria Kämäri (MDPI, 2022)
Predicting the future changes in river ice development and impacts on seasonal sediment transport requires more in-depth examination of present river ice cover growth processes. This paper therefore investigates: (1) the impacts of hydro-climatically varying years on river ice development in a Scandinavian subarctic meandering river and (2) the accuracy of existing analytical models for predicting ice thickness growth and ice decay. Stefan's ice growth equation (version by Michel et al.) and Bilello's ice decay equation are applied to varying hydro-climatic conditions experienced in the years 2013-2019. Estimates from these equations are compared with observed field conditions such as ice thicknesses, ice clearance dates and freeze-thaw days. Overall, the equations were most accurate in the winter of 2016-2017 when the maximum mid-winter snow thickness value was high, the number of freeze-thaw days was the closest to the long-term average of northern Scandinavia, and the rate of thermal snow-melt in the subsequent spring was slow. The equations would need to be adjusted to take into account expected future changes to conditions such as shorter winters, less snow formation and increased frequency of air temperatures crossing 0 degrees C.